UPAYA MENINGKATKAN HASIL BELAJAR SISWA TENTANG SEJARAH CANDI BOROBUDUR MENGGUNAKAN METODE DISCOVERY - Riyanti Riyanti; Yusya Nur Salam (PERISKOP : Jurnal Sains dan Ilmu Pendidikan, 2021)
This research is motivated by the findings in the field, in learning Social Sciences shows that students are low in instilling historical concepts, especially on the subject of the history of the Borobudur temple building, students still find it difficult to memorize history and identify the location of the Borobudur temple. This research method uses classroom action research methods. This is evidenced by the results of the tests carried out on the evaluation sheet in social studies learning which have a low average value. As an effort to improve student learning outcomes about the Borobudur temple building in this study, learning is presented through the use of the discovery method which can help students to understand the Borobudur temple building in social studies learning